2023
DOI: 10.3390/genes14112077
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Preliminary Functional Analysis of BAM (β-Amylase) Gene Family in Upland Cotton

Yanlong Yang,
Fenglei Sun,
Penglong Wang
et al.

Abstract: The β-amylase (BAM) gene family encodes important enzymes that catalyze the conversion of starch to maltose in various biological processes of plants and play essential roles in regulating the growth and development of multiple plants. So far, BAMs have been extensively studied in Arabidopsis thaliana (A. thaliana). However, the characteristics of the BAM gene family in the crucial economic crop, cotton, have not been reported. In this study, 27 GhBAM genes in the genome of Gossypium hirsutum L (G. hirsutum) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The completion of the cotton genome sequencing has provided great convenience to researchers, enabling them to deeply study the evolution and functional analysis of various gene families. In recent years, many families have been studied in cotton, such as GhCSP [ 44 ], GhWNK [ 45 ], GhTBL [ 46 ], GhBAM [ 47 ], GhACS [ 48 ], GhRF2 [ 49 ], GhGATL [ 50 ], GhANN [ 51 ], and GhWOX [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The completion of the cotton genome sequencing has provided great convenience to researchers, enabling them to deeply study the evolution and functional analysis of various gene families. In recent years, many families have been studied in cotton, such as GhCSP [ 44 ], GhWNK [ 45 ], GhTBL [ 46 ], GhBAM [ 47 ], GhACS [ 48 ], GhRF2 [ 49 ], GhGATL [ 50 ], GhANN [ 51 ], and GhWOX [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results have also indicated BAM genes were highly conservative in plants and their functions may also be similar across plants. In addition, two BAM genes from Annona atemoya , AaBAM3 , and AaBAM9 also reported localization in chloroplasts [ 48 ], while another BAM gene from upland cotton , GhBAM7 , was explored as having important roles in fiber development; the GhBAM7 protein was located in the nuclear using GFP localization [ 49 ]. PbBAM3 was cloned from a pear, which was also validated as a chloroplast-localized protein, and its function was well documented [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that starch metabolism involves a series of enzymes, among which, amylases play an essential role in starch degradation [ 13 , 14 , 15 ]. The products of starch degradation provide essential support for plant growth and development and confer increased stress tolerance [ 16 , 17 ]. Starch degradation involves α-amylase (AMY) and β-amylase (BAM) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%